Love & whiskey : the remarkable true story of Jack Daniel, his master distiller Nearest Green, and the improbable rise of Uncle Nearest - Weaver, Fawn, 1976- (Melcher Media, Inc, 2024)
"Embark on a captivating journey with Love & Whiskey. New York Times bestselling author Fawn Weaver unveils the hidden narrative behind one of America's most iconic whiskey brands. This book is a vibrant exploration set in the present day, delving into the life and legacy of Nearest Green, the African American distilling genius who played a pivotal role in the creation of the whiskey that bears Jack Daniel's name."---Amazon.